FINANCIAL RISK TOLERANT ATTITUDE: EMPIRICAL EVIDENCE FROM PAKISTAN - Bashir, Taqadus; Uppal, Shujah Tahir; Hanif, Khawar; Yaseen, Syed M.; Saraj, Kashif (European Scientific Journal, ESJ, 2013)
The study aimed to investigate the phenomena of risk tolerant attitude in response to the stock index price changes along with the demographic variables. To explore this phenomena, data was collected from the investors, bankers and household individuals whereas daily & weekly closing KSE index prices were taken from stock exchange to study the impact of the change in prices on the risk tolerant attitudes. With the help of daily & weekly regression analysis, the study concluded that in Pakistan KSE stock index prices does not have influence on individual risk tolerant attitude due to a number of reasons including lack of awareness and financial knowhow among people, financial market being in the initial developmental phase in comparison to developed nations to name few. Furthermore, due to political and economic instability people prefer to invest in gold and tend to save in government saving schemes and hold fixed deposits accounts. The study also found that men and households with higher income are more risk tolerant as compared to women and those having lower household income respectively. Age, marital status, income and education level were not found to be significant predictors of risk tolerant attitudes.